Magneto-tunelamento ressonante em super-redes de GaAs/AsGaAs - Weber Hanry Morais e Feu (2008)
In this thesis we present three works in weakly coupled semiconductor superlattices of GaAs/AlGaAs. In the first work we present an investigation of the electric field domain configuration in the sequential tunneling regime in weakly coupled superlattices in the presence of a magnetic field applied parallel to the quantum well layers. We show that, for an applied bias such that two electric field domains are present in the sample, as the magnetic field is increased a succession of discontinuous reduction in the electrical resistance is observed due to a magnetic field-induced rearrangement of the electric field domains. For a specially designed sample which has one larger quantum well, the electric field domain configuration triggered by the magnetic field remains stable after the field is reduced back to zero, in what constitutes a memory effect in the sense that the electrical resistance of the sample after application of magnetic field is different than before. In the second work we show temperature dependent magneto-transport measurements in a coupled multi-quantum well structure in the presence of a magnetic field applied parallel to the layers. We use the magnetic field to tune into resonance a thermally occupied excited subband in one well with a lower energy subband in an adjacent well, increasing the tunneling rates. In the work exhibited in Chapter 5, we perform magneto-tunneling measurements in doped GaAs/AlGaAs multi-quantum well structures, with the magnetic field appliedperpendicular to the quantum well layers. We have found evidence of a significant magnetic field-induced reduction of low energy electron scattering mechanisms, while the effect of the magnetic field on the energy relaxation paths that include longitudinal optical (LO) phononemission is much less significant. We found that while scattering assisted tunneling is inhibited by the magnetic field, resonant tunneling can be favored. The intersubband relaxation via LO phonons is not affected by the magnetic field to the point of becoming a limiting factor on the current. On the other side, the intersubband relaxation without LOphonon emission is clearly inhibited by the magnetic field to the point of becoming comparable to the resonant tunneling rate.